Information utilization pattern among male and female dairy farmers of Punjab - -, Vaishali (Indian Journal of Dairy Science, 2023)
The current research was carried out in rural Punjab to study gender desegregated information seeking and utilization behaviour as well as their role in the dairy venture. By using pretested interview schedule, the data was collected from 160 dairy farmers from three socio-cultural zones of Punjab. Gender desegregated role performance showed that male dairy farmers were more responsible for animal health care, feeding and breeding while female dairy farmers were majorly responsible for dairy finance and shed cleaning. Dairy farmers relied more upon the personal cosmopolite sources for the information followed by localite sources and impersonal cosmopolite channels. Male dairy farmer significantly sought more information from DDB, Pashu Palan Mela, State Extension Officer, PAU/KVK experts and progressive farmers as compared to females who significantly sought information more from family/relatives. In the utilization of information, female dairy farmers were ahead of their male counterparts as they significantly utilize more information sought from progressive farmers, family/relatives, localite organisations and co-operative societies. It is eye opening to note that though women sought less information, whatever they sought they utilize. Results offer food for thought to effectively transfer technologies, ideas, practices to grass root level. It is suggested to ensure equal participation of female in various extension programs so that new ideas are readily accepted and utilised by farm families. So, it can be concluded that if new technologies or innovations are transferred effectively to women then the technologies will be more readily acceptable among farm families.